Molecular Detection of Diarrheagenic Escherichia coli from Children with Acute Diarrhea in Tertiary Care Hospitals of Dhaka, Bangladesh. - Roy, Sushmita; Shamsuzzaman, SM; Mamun, Kazi Z (Asian Journal of Medical Sciences, 2013)
Objective: Multiplex PCR assay was used for diagnosis of diarrheagenic Escherichia coli (DEC) in stool samples of children (under 5 years) with acute diarrhea. Methods: Samples were collected from January 2011 to December 2011, from Dhaka Medical College Hospital and Dhaka Shishu Hospital. Multiplex PCR with five specific primer pairs to detect enteropathogenic E. coli (eae, bfp), enterotoxigenic E. coli (lt, st) and enteroaggregative E. coli (aat) were used. However, enteroinvasive E. coli, enterohemorrhagicE. coli and diffusely adhererentE. coli were not sought. Result: In total, 135 (67.5%) E. coli were isolated from 200 stool samples. The prevalence of DEC was 68 (34%). Among DEC, most frequently isolated pathotype was EPEC 40 (58.82%), followed by ETEC 24 (35.29%) and EAggEC 18 (26.47%). Among the EPEC, 5 (12.5%) were typical EPEC. Among the 68 DEC positive cases, 22 samples contained more than one pathogenic gene in various combinations. Among the combination of DEC, EPEC+ETEC combination was 6 (27.27%) followed by ETEC+EAggEC 4 (18.18%), EPEC+EAggEC and ETEC+EPEC+EAggEC were both in 3 (13.6%). Conclusion:This study shows that DEC is a common cause of childhood diarrhea in Dhaka city of Bangladesh. By using multiplex PCR assay, DEC can be diagnosed in one PCR reaction that makes a conclusive diagnosis of diarrhea. DOI: http://dx.doi.org/10.3126/ajms.v5i2.8576 Asian Journal of Medical Science, Volume-5(2) 2014: 59-66